Revitalisasi Perpustakaan Desa Melalui KKNP untuk Meningkatkan Literasi Masyarakat di Desa Taulan - Almi, Almi; Haswiwin, Haswiwin; Ramdhani, Haulia Putri; Lisda, Lisda Putri; Jannah, Miftahul Putri; Mardhatillah, Muti`ah; Naharuddin, Naharuddin; Nurlina, Nurlina; Rahma, Rahma; Sabir, Sabir; Santika, Santika; Yusuf, Zuhrah Amalia; ridwan, madinatul munawwarah (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Taulan Village Library has been revitalized to overcome challenges such as limited book collections and inadequate physical conditions. The Community Service Program (KKNP) was used to improve the library's function as a center for information and literacy. The approach involved qualitative methods such as interviews, observations, and documentation to assess the library's condition and the community's needs. The initiative resulted in an expanded book collection, physical renovations, and the organization of digital and information literacy workshops, which significantly enhanced the reading and writing skills of the community, especially students. The study concludes that revitalization not only restores the library's function but also empowers the community to sustainably improve literacy skills. The reopening of the library is expected to attract new visitors and strengthen its role as a learning center. It is crucial for the government and community to provide ongoing support for the management and development of the library in the future.